2020
DOI: 10.1029/2020gl088515
|View full text |Cite
|
Sign up to set email alerts
|

A Relationship Between ITCZ Organization and Subtropical Humidity

Abstract: Motivated by the results of idealized studies on the self‐aggregation of convection, we investigate a potential relationship between the degree of organization of the Intertropical Convergence Zone (ITCZ) and humidity based on reanalysis data. We focus on the Atlantic ITCZ and use the number of long convergence lines occurring per month to define the degree of organization. The latter shows a weak enhancement during June to August (JJA) and a large interannual variability. On an interannual time scale and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Khairoutdinov & Emanuel (2010) first discovered that the degree of convective aggregation could affect climate sensitivity because of its strong impact on top-of-atmosphere radiation balance. It was shown that self-aggregation is associated with a drying of the atmosphere in both simulations (Bretherton et al 2005) and observations (Hohenegger & Jakob 2020). This drying allows more outgoing long-wave radiation to space, cooling the planet.…”
Section: Climate Sensitivitymentioning
confidence: 87%
“…Khairoutdinov & Emanuel (2010) first discovered that the degree of convective aggregation could affect climate sensitivity because of its strong impact on top-of-atmosphere radiation balance. It was shown that self-aggregation is associated with a drying of the atmosphere in both simulations (Bretherton et al 2005) and observations (Hohenegger & Jakob 2020). This drying allows more outgoing long-wave radiation to space, cooling the planet.…”
Section: Climate Sensitivitymentioning
confidence: 87%
“…In addition to spontaneously self‐aggregating, convection can also be “forced” to aggregate by an SST gradient (Hohenegger & Jakob, 2020; Lutsko & Cronin, 2023; Müller & Hohenegger, 2020). In idealized “mock Walker” simulations, a simple SST gradient is imposed, forcing a large‐scale overturning circulation (Bretherton et al., 2006; Grabowski et al., 2000; Lutsko & Cronin, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, while the structure of low‐level convergence has been discussed in a few studies, there is still no clear consensus on how best to describe it. Theoretical and modeling studies usually emphasize a single convergence line (see e.g., Hohenegger & Jakob, 2020, for a recent example), whereby observations tend to document a more complex structure, often better idealized as a double convergence line, as shown schematically in Figure 1a and b respectively. To the extent that convergence within the ITCZ is associated with several lines of convergence that extend only a few degrees of longitude (Weller et al ., 2017), our limiting cases in Figure 1 encapsulate the idea that these lines tend to form and dissipate in the center, or toward the edges, of the rain belt.…”
Section: Introductionmentioning
confidence: 99%